The Effect of a Training Program with Rubber Ropes in Rehabilitating the fall of the Head and the Number of Times of Breathing for Young People Aged 20-22 Years - Ismael , Ammar Ali; Faraj, Adnan Radhi; Lfta, Majid Aziz; Kuraiz , Eman Abed (International Journal of Psychosocial Rehabilitation, 2020)
The strength of a healthy body improves the self-concept of individuals, as good strength enhances the functional ability of the functional organs of the human body and reduces stress and delays the emergence of fatigue, because a healthy body does not mean only the external shape of the body, but it is the mechanical relationship between the various body systems, bones, muscles, nerves and vitals, and whenever this relationship improves, the Textures are better. As for the postural deformities or deviations in the body, they result from an imbalance in the work of the muscles, ligaments and cartilage. Therefore, these deformities or deviations in the body can be corrected depending on the various rehabilitation programs and methods through which these cases can be evaluated. Among these deformities or deviations is the case of the head falling to the front, which increases the weight of the head when it is heading forward and pulls the cervical and thoracic vertebrae forward, forming a hunchback at the beginning of the thoracic vertebrae and pain in the neck area and impedes breathing.